Altered speech act indication: A problem for foreign language learners?. (October 2021) - House, Juliane; Kádár, Dániel Z.; Liu, Fengguang; Bi, Zhuo
Abstract: The aim of this study is to examine how Chinese learners of English evaluate 'altered speech act indicating functions' of conventionalised expressions normally associated with one specific speech act. In every language, there is a strongly conventionalised relationship between expressions and speech acts. The notion of altered speech act indication implies that many expressions can conventionally indicate more than one speech act, or completely lose their speech act indicating function. We explore the phenomenon of altered speech act indication by focusing on evaluations by Chinese learners of English who were presented with English examples featuring expressions associated with the speech acts of Thank and Greet, which were drawn from the British National Corpus. The respondents were asked to translate the examples to Chinese and were then interviewed about their translational choices. We devote special attention to Chinese learners of English because our previous research had revealed that conventionalised expressions in Chinese and English have very different speech act indicating capacities. The methodology of the current study is based on a tripartite system of altered speech act indication. The results of the analysis show that all types of altered speech act indication present problems for Chinese learners of English. Highlights: Provides a framework for analysing the phenomenon of altered speech act indication. Raises awareness of a key pragmatic phenomenon in foreign language teaching and learning. Reports on interviews with advanced Chinese learners of English.